2011
DOI: 10.1021/cs2003565
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Kinetic Resolution Process Employing Haloalkane Dehalogenase

Abstract: The first dynamic kinetic resolution process with a haloalkane dehalogenase is described, allowing the efficient preparation of enantiopure α-hydroxyamides from racemic α-bromoamides. A simple membrane reactor is used to separate the enzyme from the nonsoluble, polymer-based, and metal-free racemizing agent. A model substrate, N-phenyl-2-bromopropionamide, was converted to (S)-N-phenyl-2-hydroxypropionamide either with 63% yield and 95% e.e or with 78% yield and 88% e.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Furthermore, molecular dynamic simulations with LinB–substrate complexes showed that the preferred ( R )-enantiomer was more favorably bound in the active site. A dynamic kinetic resolution (DKR) procedure using polymer-based phosphonium bromide as the racemization catalyst led to highly enantioenriched α-hydroxyamides [94]. The reactions had to be conducted in a membrane reaction system to avoid inactivation of the enzyme by the racemizing polymer.…”
Section: Dehalogenasesmentioning
confidence: 99%
“…Furthermore, molecular dynamic simulations with LinB–substrate complexes showed that the preferred ( R )-enantiomer was more favorably bound in the active site. A dynamic kinetic resolution (DKR) procedure using polymer-based phosphonium bromide as the racemization catalyst led to highly enantioenriched α-hydroxyamides [94]. The reactions had to be conducted in a membrane reaction system to avoid inactivation of the enzyme by the racemizing polymer.…”
Section: Dehalogenasesmentioning
confidence: 99%
“…Haloalkane dehalogenases (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC3/8/1/5.html) are hydrolytic enzymes that cleave carbon–halogen bonds in halogenated hydrocarbons. They have important applications in bioremediation , biosensing , biosynthesis , cellular imaging and protein analysis . These enzymes possess an active site deeply buried in a hydrophobic cavity between two domains.…”
Section: Introductionmentioning
confidence: 99%
“…Haloalkane dehalogenases (HLDs;E C3.8.1.5) catalyze the hydrolytic cleavage of carbon-halogen bonds by an S N 2 mechanism (see Figure 1inthe Supporting Information). [11,12] They are useful for the enantiodiscrimination of b-bromoalkanes, a-bromoesters,and a-bromoamides, [13][14][15][16] thus yielding av ariety of enantiomerically pure intermediates that are useful for the synthesis of drugs and other bioactive compounds. [14,17,18] HLDs are good model systems for studying the principles of enantioselectivity because individual family members show different enantioselectivity and their 3D structure has been determined at atomic resolution.…”
mentioning
confidence: 99%